Pemanfaatan Desmos untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Matematika - Fitri Indriyani; Sudianto Sudianto (Papanda Publisher, 2025)
The Desmos application, as a web-based interactive graphing calculator, has been widely used in mathematics education to dynamically help visualize abstract concepts. However, studies that systematically summarize the effectiveness of Desmos in various learning contexts in Indonesia are still limited. This study aims to analyze the effectiveness of using Desmos in improving students' learning outcomes, critical thinking skills, and learning interest thru a Systematic Literature Review (SLR) approach. A total of 15 articles published between 2020 and 2025, discussing the implementation of Desmos in mathematics learning at the junior and senior high school levels, were systematically analyzed. The study results indicate that consistent use of Desmos is associated with improved learning outcomes and critical thinking skills in students, with learning mastery ranging from 75–90% and N-Gain in the medium to high category. Additionally, students showed a positive response to Desmos-assisted learning, and the developed learning materials were deemed valid and practical. Integrating Desmos with innovative learning models such as Problem-Based Learning, Creative Problem Solving, and Realistic Mathematics Education strengthens student engagement and understanding. Overall, Desmos has the potential to be an effective technology-based medium fr learning mathematics.